Brassinosteroids Interact with Auxin to Promote Lateral Root Development in Arabidopsis - Bao, Fang (American Society of Plant Biologists, 2004)
Plant hormone brassinosteroids (BRs) and auxin exert some similar physiological effects likely through their functional interaction, but the mechanism for this interaction is unknown. In this study, we show that BRs are required for lateral root development in Arabidopsis and that BRs act synergistically with auxin to promte lateral root formation. BR perception is required for the transgenic expression of the β-glucuronidase gene fused to a synthetic auxin-inducible promoter (DR5::GUS) in root tips, while exogenous BR promotes DR5::GUS expression in the root tips and the stele region proximal to the root tip. BR induction of both lateral root formation and DR5::GUS expression is suppressed by the auxin transport inhibitor N-(1-naphthyl) phthalamic acid. Importantly, BRs promote acropetal auxin transport (from the base to the tip) in the root. Our observations indicate that BRs regulate auxin transport, providing a novel mechanism for hormonal interactions in plants and supporting the hypothesis that BRs promote lateral root development by increasing acropetal auxin transport.